Biomineralized Composite Liquid Crystal Fiber Scaffold Promotes Bone Regeneration by Enhancement of Osteogenesis and Angiogenesis - Yi Zhan (Frontiers Media S.A., 2021)
Liquid crystals (LCs) are appealing biomaterials for applications in bone regenerative medicine due to their tunable physical properties and anisotropic viscoelastic behavior. This study reports a novel composite poly (L-lactide) (PLLA) scaffold that is manufactured by a simple electrospinning and biomineralization technique that precisely controls the fibrous structure in liquid LC phase. The enriched-LC composites have superior mineralization ability than neat PLLA; furthermore BMSC cells were inoculated onto the HAP-PLLA/LC with hydroxyapatite (HAP) composite scaffold to test the capability for osteogenesis in vitro. The results show that the PLLA/LC with HAP produced by mineralization leads to better cell compatibility, which is beneficial to cell proliferation, osteogenic differentiation, and expression of the angiogenic CD31 gene. Moreover, in vivo studies showed that the HAP-PLLA/LC scaffold with a bone-like environment significantly accelerates new and mature lamellar bone formation by development of a microenvironment for vascularized bone regeneration. Thus, this bionic composite scaffold in an LC state combining osteogenesis with vascularized activities is a promising biomaterial for bone regeneration in defective areas.